UJI AKTIVITAS SITOTOKSIK EKSTRAK METANOL BUAH KETUMBAR (Coriandrum sativum Linn) TERHADAP ARTEMIA SALINA LEACH DENGAN UJI BSLT (Brine Shrimp Lethality Test) - Yulia, Mega; Anggraini, Rani; Farizal, Farizal (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2020)
Coriander is a common herb can be used as traditional medicine. One of the expected benefits of Coriander fruits is an anti-cancer. This study aims to determine the cytotoxic activity of Coriander extract (Coriandrum sativum Linn) on shrimp larvae (Artemia salina Leach) with the BSLT (Brine Shrimp Lethality Test) method. Coriander fruits was extracted using methanol solvent and maceration method, then concentrated it with a rotary evaporator until a thick extract. Cytotoxic activity test used methanol extract with several concentration : 1,000 ppm, 100 ppm, 10 ppm, and 1 ppm. The result of this research reveal that methanol extract of Coriander fruits has cytotoxic activity with LC50 value is 32.35 ppm.